Electrochemical Performance of Calcium Cobaltite Nano-Plates - Kim, Dong-Wan; Ko, Young-Dae; Park, Jong-Sung; Je, Hae-June; Son, Ji-Won; Kim, Joosun (AMER SCIENTIFIC PUBLISHERS, 2009)
The use of nanostructured materials in Li-ion batteries is desirable from the point of view of achieving enhanced performance, due to the shorter Li-ion diffusion distance and the small dimensional changes upon cycling. Herein, the nanocrystalline calcium cobaltite (Ca(3)Co(4)O(9)) powders were prepared by the Pechini process. The obtained nano-plate powders have a thickness of the order of 10-50 nm and a diameter of around 300 nm. We investigated the electrochemical properties of Ca(3)Co(4)O(9) as a potential new anode material with high capacity for Li-ion batteries. In addition, the mechanism of Li reactivity was successfully explained using high resolution transmission electron microscopy. The full reduction of Ca(3)Co(4)O(9) by lithium leads to the destruction of crystal structure and subsequent formation of a nanocomposite electrode containing Co, Li(2)O, CaO, and a polymeric layer. The inactive CaO matrix is expected to mitigate the aggregation of the Co nanoparticles on continued cycling, thereby improving the capacity retention.
Keywords: LI-ION BATTERIES; ANODE MATERIALS; ELECTRODE MATERIALS; OXIDES; CONVERSION; CO3O4; TIN